Analisa Algoritma C4.5 Terhadap Penentuan Rekomendasi Penerima Beasiswa - Wahyu Susanto; Astriana Mulyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Scholarships are financial assistance with the intention of being used as a means of continuing their education and are usually given by foundations, companies or government agencies. Scholarships are in the form of funds used to assist underprivileged students in continuing their duties in completing their education. Therefore, the granting of scholarships must be right on target to recipients who really deserve and deserve it. The large number of potential recipients makes the selection process take a long time. In this case, the use of data mining methods can be used as a solution to simplify the selection process. The C4.5 algorithm is the algorithm that will be used in this research. The data used are the names of students, class, parents' income, dependents of parents, and average grades of report cards. Data mining processing on a training data will produce a decision tree. The evaluation method carried out in this test obtained 90% accuracy value data, this can be evidence that the C4.5 algorithm is accurate enough to provide scholarship recommendations.